Synthesis and Characterization of Micro-nano Carbon Filler from Jatropha Seeds - Law, Perry Nyuk Khui; Md. Rezaur, Rahman; Sinin, Bin Hamdan; Elammaran, Jayamani; Muhammad Khusairy, Bin Bakri; Khairuddin, Sanaullah (NC State University, 2020)
iochar was synthesized from biomass (jatropha seeds) through a low microwave pyrolysis temperature of 180 °C with microwave power of 2kW. A ball milling process reduced the jatropha seed biochar size and converted it into micro-nano carbon biofiller. After ball milling, the biochar size was reduced from 1 to 3 mm to the 10 µm to 600 nm range, which is around a 90% reduction in size. Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and Brunauer-Emmett-Teller (BET) analysis were used to determine the jatropha seed biofillers properties with respect to the ball milling processes. BET results revealed increasing surface area from 0.10 to 3.67 m2/g, and EDS results revealed the elemental composition of the jatropha seed biofillers. The carbon mass percentage increased from 72.6 to 81.2%. Both results were after ball milling for 30 hours. The FTIR results revealed an increase in transmittance intensity and some reduction in peaks after ball milling. Production of micro-nano carbon fillers from microwave pyrolysis jatropha seeds biochar are applicable as reinforcement fillers for high strength composite material fabrications. Scanning electron microscopy, EDS, FTIR, and BET analysis results indicated size reduction of the biochar with increased carbon content from 72.6 to 81.2% as surface area increased from 0.10 to 3.67 m2/g after 30 hours of ball milling.